A note on Topological indices and coindices of disjunction and symmetric difference of graphs - Alameri, Abdu; Alsharafi, Mohammed; Ali, Esmail; Gumaan, Mohammed S. (Elsevier, 2021)
In this paper we compute the correct values of Zagreb indices and the forgotten index of two classes of composite graphs disjunction and symmetric difference. In this way we correct some previously reported formulas given in https://doi.org/10.1016/j.dam.2008.06.015, https://doi.org/10.1016/j.dam.2010.05.017 and https://link.springer.com/article/10.1186/s40064-016-1864-7. As a consequence, we compute the correct values of the respective.